Lesbophobia, an analysis about experiences of lesbians artists and activists - Orellana Rojas, Zicri; Barrera Mansilla, María (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2021)
Lesbophobia is a violence phenomenon against lesbians that has little information, systematization and scientific knowledge that allows to account for the problem, and in this way, offer relevant information to take actions at the social and political level. This article offers an approach to the problem, taking into account the experiences of lesbian artists and activists who recognize lesbophobia as an important part of their lives, since this both damages and makes their lives difficult .From the stories of lesbians, it has been possible to organize a body of knowledge that allows us to identify that there are several types of violence, which threaten the very existence of lesbians. In consequence, 7 types of violence were identified: bumps, expulsion, stigmatization, misogyny, censorship and silence, economic violence and impoverishment, promotion of guilt and pressure. These types of violence occur in at least 4 settings: family, school, church and street. And as for the triggers of violence, they observe that the exit from silence, especially within the family; and the aesthetics ,visibly out of femininity, triggers violent practices from people. This description of violence has also allowed to divide it into 3 forms of lesbophobia: explicit, covert and internalized. To make the reflection on this phenomenon, feminist concepts have been taken that provide a field of theoretical analysis for understanding. Above all, because this is about a problem that affects lesbian women, who experience a double condition of discrimination, and when it comes to women belonging to an ethnic group, a triple condition of discrimination and risk of violence. For this reason, the organization of lesbian thought and lesbian experience is necessary, so that measures and actions can be taken in favor of their lives.
Keywords: lesbians; lesbian hate; lesbophobia; violence; heterosexual (straight).